CVD growth and properties of boron phosphide on 3C-SiC - Padavala, Balabalaji; Frye, C.D.; Wang, Xuejing; Raghothamachar, Balaji; Edgar, James H. (My University, 2016)
Improving the crystalline quality of boron phosphide (BP) is essential for realizing its full potential in semiconductor device applications. In this study, 3C-SiC was tested as a substrate for BP epitaxy. BP films were grown on 3C-SiC(100)/Si, 3C-SiC(111)/Si, and 3C-SiC(111)/4H-SiC(0001) substrates in a horizontal chemical vapor deposition (CVD) system. Films were produced with good crystalline orientation and morphological features in the temperature range of 1000–1200 °C using a PH3+B2H6+H2 mixture. Rotational twinning was absent in the BP due to the crystal symmetry-matching with 3C-SiC. Confocal 3D Raman imaging of BP films revealed primarily uniform peak shift and peak widths across the scanned area, except at defects on the surface. Synchrotron white beam X-ray topography showed the epitaxial relationship between BP and 3C-SiC was (100)(100)〈011〉〈011〉BP||(100)(100)〈011〉〈011〉3C-SiC and (111)(111)View the MathML source〈112̅〉BP||(111)(111)View the MathML source〈112̅〉3C-SiC. Scanning electron microscopy, Raman spectroscopy and X-ray diffraction analysis indicated residual tensile strain in the films and improved crystalline quality at temperatures below 1200 °C. These results indicated that BP properties could be further enhanced by employing high quality bulk 3C-SiC or 3C-SiC epilayers on 4H-SiC substrates.
Citation: CVD growth and properties of boron phosphide on 3C-SiC, B. Padavala, C.D.Frye, X. Wang, B. Raghothamachar, and J.H. Edgar, Journal of Crystal Growth, volume 449 pp. 15-21 (2016).
Keywords: B2. Semiconducting III–V materials; A3. Hydride vapor phase epitaxy; A1. Characterization; A1. High resolution X-ray diffraction; A1. X-ray topography; A1. Defects